Unmet clinical needs in the management of advanced melanoma: findings from a survey of oncologists. (29th July 2015) - Jones, C.; Clapton, G.; Zhao, Z.; Barber, B.; Saltman, D.; Corrie, P.
<x xml:space="preserve">Abstract</x> Advanced melanoma is a life‐threatening cancer with limited life expectancy. The recent introduction of new targeted systemic therapies has provided clinicians with the means to potentially extend survival for the first time. However, the chance of cure remains very low and treatment‐induced toxicity is well described. This qualitative study was undertaken to evaluate clinicians' assessment regarding the key concerns in managing advanced melanoma following the introduction of these new treatments. Three hundred and forty‐three oncologists were surveyed online between August and November 2012 (in 11 countries) and March and April 2013 (in an additional country). Analysis of free‐text responses identified 23 clinical issues of concern across all countries. Of these, the most common clinical concerns were drug toxicity and tolerability, followed by limited treatment effectiveness and limited treatment options. These results suggest that despite the promise of the two new agents in the field, clinicians are still concerned about the limitations of current treatment options, recognising that there remains a significant unmet need in the treatment of advanced melanoma.